2020
DOI: 10.1039/d0sc03115a
|View full text |Cite
|
Sign up to set email alerts
|

Neuraldecipher – reverse-engineering extended-connectivity fingerprints (ECFPs) to their molecular structures

Abstract: Protecting molecular structures from disclosure against external parties is of great relevance for industrial and private associations, such as pharmaceutical companies. Within the framework of external collaborations, it is common...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…20 This work is, in that sense, loosely related to our previously published NeuralDecipher model that is able to reverseengineer molecular structures from folded extended-connectivity fingerprints. 21 Both works rely on the autoencoder by Winter et al 20 (Figure 2). This autoencoder was trained to translate an input molecule SMILES representation into the corresponding canonical SMILES representation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 This work is, in that sense, loosely related to our previously published NeuralDecipher model that is able to reverseengineer molecular structures from folded extended-connectivity fingerprints. 21 Both works rely on the autoencoder by Winter et al 20 (Figure 2). This autoencoder was trained to translate an input molecule SMILES representation into the corresponding canonical SMILES representation.…”
Section: Methodsmentioning
confidence: 99%
“… 20 This work is, in that sense, loosely related to our previously published Neuraldecipher model that is able to reverse-engineer molecular structures from folded extended-connectivity fingerprints. 21 Both studies rely on the autoencoder developed by Winter et al 20 ( Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, while we have argued that the amount of public data is increasing at a fast pace, most of the structural activity/ property relationship data are still generated by commercial research organizations, publishers, and pharmaceutical companies [95][96][97], which often consider the generated data as a differentiating asset to be kept confidential. Recent developments have shown that molecular structures can often be partially recovered from molecular descriptors, which may further complicate data sharing even at the latent feature level [98]. Attempts to overcome such limitations, for example, by developing federated and intellectual property (IP)preserving learning techniques, are underway [99].…”
Section: Article Highlightsmentioning
confidence: 99%
“…Recently, there was a new publication called ChemPix [ 15 ], a deep learning-based method that was developed to recognize hand drawn hydrocarbon chemical structures. Another recent publication describes SMILES generation from images [ 16 ] where an encoder–decoder method with a pre-trained decoder is used from previous work [ 17 ]. These contributions demonstrate an increasing interest in this field of research.…”
Section: Introductionmentioning
confidence: 99%